STUDI PENGARUH PENAMBAHAN ABU SEKAM PADI TERHADAP KUAT TEKAN BETON - Samsudin Samsudin; Sugeng Dwi Hartantyo (Jurnal Teknika, 2017)
Rice husk is the waste from the rice mill has a dominant silica content that is equal to 93% and almost the same content of silica contained in the microsilica manufactured. By its nature when mixed into the concrete mix will improve the characteristics of concrete. In this research, rice husk ash was added to the concrete mixture of Fc 'K-175 Kg / cm2 with a variation of 0%, 8%, 10%, and 12% husk ash ash taken based on the weight of cement. This research aims to determine the value of concrete compressive strength achieved from rice husk ash mixture in K-175 Kg / cm2 concrete. Concrete mortar design using ASTM method. Test specimens were made for each addition of the percentage of husk ash is as much as 3 samples, with cylinder mold size 15 cm diameter with height 30 cm. Based on Table 4:22 in the results obtained that there is a decrease in strength on each addition of ash rice husk level. It is known that the normal compressive strength of 28 days old concrete is 226,47 kg / m2 and the lowest compressive strength is in the addition of rice husk ash 12% age 28 day that is 129,41 kg / m2